Depresión y su incidencia en el rendimiento académico en un paciente de 14 años - Bajaña Hernandez, Kerly Stefany (2019)
The present case study, the objective is to determine the incidence of depression in academic performance in a fourteen years olds patient treated at the Babahuyus Educational Unit, who has depressive symptomatology which was applied to the Beck test that is determined by measuring the level of depression and the Raven test that is characterized by rating the IQ, and in this way determine if it is related to your academic performance. Therefore, due to the analysis made to it, through the interviews applied and its diagnostic characteristic according to the manual of the classification of mental disorders CEI-10, it was deduced that the patient is in an episode of moderate depression. Which was proposed to make a psychotherapeutic plan through cognitive behavioral therapy, through the course of three sessions, so that the patient overcome her depression by improving her mood and functional activities.